Source of contaminant microorganisms in in vitro culture at Sub lab. Biology, Central Laboratory of Mathematics and Sciences, Sebelas Maret University - ARI SUSILOWATI; SHANTI LISTYAWATI (Biodiversitas Journal of Biological Diversity, 2001)
The objectives of the research were to know the species and the most dominant microorganisms that become a source of contamination in in vitro culture at Sub lab Biology, central laboratory of Sebelas Maret University. As in many general laboratory, there were many microorganisms that able to contaminate in vitro culture coming from air, dusts, or from the contaminated experimental materials such as plants or fruits. A qualitative descriptive method was used in the research, involving many steps of making pure culture and identification of microorganisms macroscopically or microscopically. In the research found six microorganisms potentially contaminate in vitro culture, that are generally from groups of fungi (mold), such as Mucor, Rhizopus, Cladosporium, Aspergillus, Dictyostelium and Saccharomyces. Mucor and Rhizopus were the most contaminants present in all contaminated in vitro culture.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey Words: in vitro culture, contamination, fungi